1, 2, 4-Triazole-based anticonvulsant agents with additional ROS scavenging activity are effective in a model of pharmacoresistant epilepsy. (1st January 2020) - Kaproń, Barbara; Czarnomysy, Robert; Wysokiński, Mariusz; Andrys, Rudolf; Musilek, Kamil; Angeli, Andrea; Supuran, Claudiu T.; Plech, Tomasz
Abstract: There are numerous studies supporting the contribution of oxidative stress to the pathogenesis of epilepsy. Prolonged oxidative stress is associated with the overexpression of ATP-binding cassette transporters, which results in antiepileptic drugs resistance. During our studies, three 1, 2, 4-triazole-3-thione derivatives were evaluated for the antioxidant activity and anticonvulsant effect in the 6 Hz model of pharmacoresistant epilepsy. The investigated compounds exhibited 2-3 times more potent anticonvulsant activity than valproic acid in 6 Hz test in mice, which is well-established preclinical model of pharmacoresistant epilepsy. The antioxidant/ROS scavenging activity was confirmed in both single-electron transfer-based methods (DPPH and CUPRAC) and during flow cytometric analysis of total ROS activity in U-87 MG cells. Based on the enzymatic studies on human carbonic anhydrases (CAs), acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), one can assume that the herein investigated drug candidates will not impair the cognitive processes mediated by CAs and will have minimal off-target cholinergic effects.